Northwest view of the ancient structure of Merchant Taylors' Hall, with the adjoining almshouses in Threadneedle Street - Goodman, William (Tufts Archival Research Center, 2008)
From a drawing taken by William Goodman in 1599. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 2.